Foreign Exchange Market Pressure, Exchange Rate and Trade Balance in Nigeria: Is There Evidence of the J-Curve Effect? - Akighir, David Terfa (Journal of Developing Economies, 2023)
The paper examined the relationship between the pressure in the exchange market, exchange rate, and trade balance in Nigeria to ascertain whether or not the J-Curve effects exist. The investigation was anchored on the Marshal-Lerner and the J-Curve theories using annual time series data from 1986 to 2021. The Structural Vector Autoregressive (SVAR) technique was employed, and the findings revealed that the pressure in the exchange market exerts a strong contemporaneous positive effect on the exchange rate in the country. Also, the findings showed that the exchange rate has a strong contemporaneous negative effect on the trade balance. Furthermore, the long-run results indicated that the exchange rate has a positive but weak effect on the country's trade balance. Based on these findings, it was concluded that the relationship that exists among foreign exchange market pressure, exchange rate, and balance of trade suggests the potentiality of the J-Curve effects in the economy. The study recommended that local production of goods and services in Nigeria should be strengthened so that the depreciation of the naira would improve the trade balance. In the event of naira depreciation, domestic consumers could redirect their demand to the consumption of locally produced goods and services. Also, local production, especially in manufacturing and agricultural processing, should be encouraged, and the quality of the products be enhanced for competitive exportation to improve the trade balance in the country. The policy implication is that policymakers can leverage naira depreciation as a policy tool to enhance Nigeria's balance of trade.